Editorial: How do you diagnosis and manage sports-related concussion (SRC) in road cycling? A Plan for developing SRC-assessment and management protocols within road cycling - Heron, N. (Journal of Science and Cycling, 2020)
Sports-related concussion (SRC) is a common injury within elite road cycling and SRC is typically assessed and managed with a SCAT5. However the SCAT5 cannot be applied to road cycling in its current format and the cycling community therefore need to consider modifications or indeed alternatives to the SCAT5 to allow adequate assessment and management of SRC within road cycling. Potential solutions to consider to improve SRC assessment and management in road cycling include: 1) a SRC consensus meeting to allow modification of the SCAT5 for road cycling; 2) rule alterations to allow `pitch-side` SRC assessment during races; 3) epidemiological injury surveillance within road cycling to better understand the issues around SRC; and, 4) better use of technologies to help diagnose SRC. We hope that these solutions can go some way to bridging the gap between SRC assessment and management between our own sport of road cycling and those with maturing SRC protocols, such as rugby union.